2021
DOI: 10.1021/acs.est.1c05958
|View full text |Cite
|
Sign up to set email alerts
|

Acid- and Base-Mediated Hydrolysis of Dichloroacetamide Herbicide Safeners

Abstract: Safeners are used extensively in commercial herbicide formulations. Although safeners are regulated as inert ingredients, some of their transformation products have enhanced biological activity. Here, to fill gaps in our understanding of safener environmental fate, we determined rate constants and transformation products associated with the acid- and base-mediated hydrolysis of dichloroacetamide safeners AD-67, benoxacor, dichlormid, and furilazole. Second-order rate constants for acid- (HCl) and base-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In contrast, over the same time period, only 40.6 ± 0.8% of benoxacor transformed in aqueous systems where benoxacor was the sole carbon source and 48 ± 3% in systems containing humic acid, a more recalcitrant carbon source unlikely to facilitate cometabolism . Only 39.0 ± 1.3% of the total benoxacor concentration was transformed in abiotic controls, likely due to hydrolysis; the decay followed first-order kinetics at a rate consistent with our prior studies . Batch tests for the other safeners studied were conducted as described in the presence of acetate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, over the same time period, only 40.6 ± 0.8% of benoxacor transformed in aqueous systems where benoxacor was the sole carbon source and 48 ± 3% in systems containing humic acid, a more recalcitrant carbon source unlikely to facilitate cometabolism . Only 39.0 ± 1.3% of the total benoxacor concentration was transformed in abiotic controls, likely due to hydrolysis; the decay followed first-order kinetics at a rate consistent with our prior studies . Batch tests for the other safeners studied were conducted as described in the presence of acetate.…”
Section: Resultsmentioning
confidence: 99%
“…Dichloroacetamide safeners are coapplied with chloroacetamide herbicides to selectively protect crops from unintended herbicide toxicity. Due to their extensive use (>8 × 10 6 kg/year globally) and hydrophilic nature, the four most common dichloroacetamides (AD-67, benoxacor, dichlormid, and furilazole) have been detected in surface waters throughout the midwestern U.S., yet their environmental fates remain largely underinvestigated. ,− Existing research, including studies by our groups, indicates that safeners can transform in the environment to yield products with increased biological activity and, in some cases, increased toxicity. ,, For example, dichloroacetamides in iron-rich anaerobic environments can undergo reductive dechlorination to yield more toxic products, including formation of CDAA (known as allidochlor or 2-chloro-N,N-bis­(prop-2-enyl)­acetamide; an herbicide banned in the United States due in part to human health concerns) from dichlormid, as well as monochloro-benoxacor (toxic toward insect larvae; LOEC = 0.1 mg kg –1 ) from benoxacor. ,, Recently, we probed dichloroacetamides' environmental fate, focusing on photolysis and hydrolysis. , Only benoxacor transformed by direct photolysis, and hydrolysis rates were slow and only environmentally relevant under basic (pH 10–11) conditions. , Thus, there are potentially significant environmental fate processes relevant to dichloroacetamide safeners, notably microbial biotransformation, that remain uncharacterized and may yield transformation products of concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, dichloroacetamide safeners can undergo photolysis (Kral et al, 2019;Su et al, 2019), hydrolysis (McFadden et al, 2022), abiotic reductive dechlorination (Ricko et al, 2020;Sivey & Roberts, 2012;Xu et al, 2020Xu et al, , 2022, and *Indicates significant difference compared with controls (shown as 0 for each figure). AD, AD-67.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, dichloroacetamide safeners can undergo photolysis (Kral et al, 2019; Su et al, 2019), hydrolysis (McFadden et al, 2022), abiotic reductive dechlorination (Ricko et al, 2020; Sivey & Roberts, 2012; Xu et al, 2020, 2022), and biotransformation (Abu‐Qare & Duncan, 2002) in the environment. These processes can result in the safener changing into structures like those of herbicides, which could be more toxic than the parent (Abu‐Qare & Duncan, 2002; Sivey & Roberts, 2012).…”
Section: Discussionmentioning
confidence: 99%